Efficacy, safety and predictors of combined fruquintinib with programmed death-1 inhibitors for advanced microsatellite-stable colorectal cancer: A retrospective study - Zhang, Weijie; Zhang, Zhongyue; Lou, Shitong; Li, Donghui; Ma, Zhijun; Xue, Lei (Frontiers in Oncology, 2022)
Background Research findings have revealed that combining anti-angiogenesis inhibitors with programmed death-1(PD-1) inhibitors can reverse the immunosuppressive tumor microenvironment and enhance the antitumor immune response. To explore the therapeutic options for breaking immune tolerance in microsatellite stability (MSS) or mismatch repair-proficiency (pMMR) advanced colorectal cancer (CRC), we assessed the efficacy, safety and predictors of the fruquintinib and PD-1 inhibitors combination in patients with MSS/pMMR advanced CRC in a real-world environment. Methods We conducted a single-center retrospective study by collecting relevant data on patients with MSS/pMMR advanced CRC who received fruquintinib coupled with PD-1 inhibitors in the First Affiliated Hospital of Zhengzhou University between August 2019 and November 2021, focusing on progression-free survival. Results We enrolled 110 eligible patients in this study between August 2019 and November 2021. At the deadline (January 20, 2022), 13 patients had objective responses. The objective response rate was 11.8% (13/110, 95% confidence interval [CI]: 6.4-18.2), the disease control rate was 70.0% (82/110, 95% CI: 60.9-78.2), and the progression-free survival was 5.4 months (95% CI: 4.0-6.8). Liver metastases (hazard ratio [HR]: 0.594, 95% CI: 0.363-0.973, P<0.05), alkaline phosphatase elevation (ALP>160U/L) (HR: 0.478, 95%CI: 0.241-0.948, P<0.05), fibrinogen elevation (FIB>4g/L) (HR: 0.517, 95% CI: 0.313-0.855, P<0.05), and an increase in the ALP level from the baseline after treatment (HR: 1.673, 95% CI: 1.040-2.690, P<0.05) were negative predictors of the progression-free survival. A total of 101 of 110 patients experienced treatment-related adverse events, including 14 who experienced grade 3 or above treatment-related adverse events, and no treatment-related deaths occurred. Hypertension was the most frequently encountered grade 3 treatment-related adverse event. Conclusion Fruquintinib combined with PD-1 inhibitors has antitumor activity and manageable safety in treating patients with MSS/pMMR advanced CRC. Liver metastases, ALP level and FIB level might be a prediction of the patient response to this therapy.